2004
DOI: 10.1161/01.atv.0000134378.86443.cd
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Derived Interleukin 10 Is Required for Protection Against Atherosclerosis in Low-Density Lipoprotein Receptor Knockout Mice

Abstract: Background— Atherosclerosis is an immunoinflammatory disease. Here we examined the role of leukocyte-derived interleukin 10 (IL-10) on advanced atherosclerosis development in low-density lipoprotein receptor knockout (LDLr−/−) mice. Methods and Results— Bone marrow cells harvested from C57BL/6 IL-10−/− and IL-10+/+ mice were transplanted into irradiated male LDLr−/− mice. Four weeks after transplantation, mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 26 publications
6
90
0
2
Order By: Relevance
“…Selective silencing of STAT3 in mouse macrophages and neutrophils increases susceptibility to endotoxic shock and promotes chronic entercolitis (27,43). The antiinflammatory cytokine IL-10 suppresses the production of inflammatory cytokines in macrophages through STAT3, and IL-10 knockout mice have chronic inflammation and increased atherosclerosis (26,44). Here we found that activating STAT3 without cholesterol efflux by the interaction of apoA-I/ABCA1 significantly inhibited proinflammatory cytokine expression in macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…Selective silencing of STAT3 in mouse macrophages and neutrophils increases susceptibility to endotoxic shock and promotes chronic entercolitis (27,43). The antiinflammatory cytokine IL-10 suppresses the production of inflammatory cytokines in macrophages through STAT3, and IL-10 knockout mice have chronic inflammation and increased atherosclerosis (26,44). Here we found that activating STAT3 without cholesterol efflux by the interaction of apoA-I/ABCA1 significantly inhibited proinflammatory cytokine expression in macrophages.…”
Section: Discussionmentioning
confidence: 60%
“…Another possible explanation may be that AIF-1 overexpression biases the immune response from Th1 to Th2 as we have demonstrated in in vitro experiments (14) and in the trinitrobenzene sulphonateinduced colitis model in mice (15). Since atherosclerosis is aggravated in the Th1 condition, the Th2-biased immune deviation (elevation of IL-6 and IL-10 levels) may exert regulatory influences on atherogenesis in the AIF-1 Tg environment (32)(33)(34)(35)(36). However, AIF-1 transfectants also produce IL-12, a pro-atherogenic factor, upon stimulation with LPS (14).…”
Section: Discussionmentioning
confidence: 96%
“…This is exemplified in recent murine atherosclerosis studies on IFN-␥ deficiency in atherosclerosis in the LDL receptordeficient mouse (40). Lesion phenotype is dramatically changed with modulation of IL-10 signaling and attenuation or alteration of TGF ␤ signaling (42,43,47,49).…”
Section: Additional Commentsmentioning
confidence: 94%
“…When LDL receptor-deficient mice are transplanted with bone marrow overexpressing IL-10 in T-cells, atherosclerosis is reduced (42). In contrast, the transplantation of IL-10-deficient bone marrow into LDL receptor-deficient mice led to a marked increase in lesion development at several sites, and these lesions were rich in macrophages and lymphocytes (43). Nuclear factor B (NF-B) mediates many proinflammatory effects.…”
Section: Downloaded Frommentioning
confidence: 99%